Plasma kallikrein: the bradykinin-producing enzyme - Björkqvist, Jenny; Jämsä, Anne; Renné, Thomas (Thrombosis and Haemostasis, 2013)
Plasma prekallikrein is the liver-derived precursor of the trypsin-like serine protease plasma kallikrein (PK) and circulates in plasma bound to high molecular weight kininogen. The zymogen is converted to PK by activated factor XII. PK drives multiple proteolytic reaction cascades in the cardiovascular system such as the intrinsic pathway of coagulation, the kallikrein-kinin system, the fibrinolytic system, the renin-angiotensin system and the alternative complement pathway. Here, we review the biochemistry and cell biology of PK and focus on recent in vivo studies that have established important functions of the protease in procoagulant and proinflammatory disease states. Targeting PK offers novel strategies not previously appreciated to interfere with thrombosis and vascular inflammation in a broad variety of diseases.